Settlement of Grant Disputes in the Perspective of Islamic Law (Analysis of Decision Number: 48/Pdt.Sus/2011 About Cancellation of Grant) - Suaidi (QURU’: Journal of Family Law and Culture, 2024)
In recent decades, grant disputes have attracted considerable attention because the decisions often present debates and the decisions concluded need to reach decisions that are just and in accordance with applicable legal principles. This article will analyse Decision Number: 48/Pdt.Sus/2011 on grant cancellation. The method used in this research uses a normative juridical approach method by examining the results of the decision. This research aims to understand how Islamic law is applied in grant dispute cases, particularly in the context of grant cancellation between parents and their children. Through this case study, the legal bases used by the court were analysed, including the Compilation of Islamic Law (KHI) and the Compilation of Sharia Economic Law (KHES). This study found that the court's decision refers to Article 212 of the KHI and Article 712 of the KHES which stipulates that the grantor can withdraw the grant after the handover has been carried out on the condition that the recipient agrees to it, this provision does not apply to grants from parents to their children. Grants from parents to their children can be withdrawn as long as the child is still alive, according to article 714 paragraph (2) KHI.